DEWI SRIKANDI: INNOVATIVE SUPPORT THAT CREATES INDEPENDENT CADRES FOR DETECTING HIGH-RISK PREGNANCY COMPLICATIONS - Indah Christiana; Endah Kusuma Wardani (JOURNAL EDUCATIONAL OF NURSING(JEN), 2026)
High-risk pregnancy refers to conditions in which the pregnant mother or fetus has factors that increase the likelihood of complications during pregnancy. Efforts for high-risk pregnancies in maternal health involve the services and care of pregnant women through integrated ANC services via the Dewi Srikandi program. This study aims to determine whether there is an effect of the Dewi Srikandi innovation mentoring on the independence of cadres in early detection efforts of high-risk pregnancy complications in the Work Area of Parijatah Kulon Health Center. The research design used is a quasi-experiment with a two-group pretest-posttest design with a control group. The population in this study consists of all cadres in the work area of Parijatah Kulon Health Center, amounting to 249 people, with a sample of 70 people taken through proportional random sampling. The research instrument used a questionnaire, and the collected data were tested for homogeneity, resulting in heterogeneous data, thus the Mann Whitney test was used. The research results showed an increase in the independence of cadre members in the intervention group by 25.72 and in the control group by 14. The Mann Whitney test results showed a p-value of 0.000 <0.05, meaning that there is an effect of the Dewi Srikandi innovation mentoring on cadre independence in efforts to detect early complications in high-risk pregnant women. Based on these research results, the community health center continues to provide continuous mentoring of the Dewi Srikandi program, and the cadres are more active in seeking information on high-risk pregnancies.